A Critical Review of Spiritual Well-Being Scales: Implications for Research, Practice, and Education in Rehabilitation Counseling. (April 2019) - Lu, Junfei; Lo, Chu-Ling; Bang, Na Mi; Romero, Devon
The primary goal of rehabilitation counseling services is to holistically enhance quality of life (QOL) of persons with disabilities. However, the spiritual dimension of QOL may be the area least attended to by both rehabilitation counselors and counselor educators. It is imperative to raise attention to and understanding of this dimension and specifically its main indicator—spiritual well-being (SWB). In response, the authors of this study reviewed and examined 15 SWB scales regarding scale domains, item generation, selected sample, scaling approaches, as well as psychometric properties (i.e., reliability and validity). The results raised various issues that should be considered by professionals in rehabilitation counseling when studying SWB and its measurement. Implications were provided with regard to research, practice, and teaching on the topic of SWB in rehabilitation counseling.